Answer:
0
Explanation:
We are given a function
.
To find its inverse, we will put this function equal to y (or any other variable) and make x the subject.
![y = 3(x+2)-4](https://img.qammunity.org/2019/formulas/mathematics/high-school/x2e738vkoi9ccbyury47q8bf6k9vesa68y.png)
![y+4 = 3x+6](https://img.qammunity.org/2019/formulas/mathematics/high-school/wj0mtih2pozqrwtlkll4bsr4s29mz5abpt.png)
![y+4-6 = 3x](https://img.qammunity.org/2019/formulas/mathematics/high-school/brgopg9dvmdn6s9qeqq36vn4u8bdjchwym.png)
![(y-2)/(3) = x](https://img.qammunity.org/2019/formulas/mathematics/high-school/q7tdln1dfxpfbwsrdl2wtdv0mqw3f49uv6.png)
So,
![f'(x) = (x-2)/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/bohi8hdzx0frpc8s8n01slviwf6vjs5ptt.png)
Now put x = 2 in this to get the value of inverse of this function:
![= 0](https://img.qammunity.org/2019/formulas/biology/middle-school/t09u0hztnygni2u8878bhego1gux3vn9fm.png)
Therefore, the value of the inverse of this function when x = 2 is 0.